Synthesis, characterization, and performance of novel phosphate-modified polymers as air-entraining agents. (30th January 2020) - Ma, Jianfeng; Shang, Yazhuo; Peng, Changjun; Liu, Honglai; Zheng, Shuzhen; Zhao, Hongxia; Qi, Shuai; Ran, Qianping
Highlights: Phosphate-modified polymers with different aryl substitution were synthesized. Hydrophobic groups in polymer obviously affect the foam performance of surfactant. Demonstrating better air-entraining performance than commercial reagent SA-1. Abstract: Air content can greatly affect the properties of concrete, therefore, the development of high efficient air-entraining agents is important. In this work, novel phosphate-modified polymers with different aryl substitutions were synthesized and used as highly efficient air-entraining agents. The structure of polymers was characterized by 1 H NMR and IR spectra. The foamability and foam stability of the different polymeric surfactants were tested in solutions. Surfactants with large steric hindrance, such as APP-6, showed superior performance of foamability and foam stability. In view of the excellent foamability properties of synthesized polymers in aqueous solution, the application of these polymers used in cement mortar as air-entraining agents were also evaluated for practical application. The surface tension, theoretical calculation and dynamic light scattering test for these polymeric surfactants were also studied. The synthetic aryl-polyether-phosphate surfactants showed higher surface activity, foamability, foam stability, and air-entraining performance compared with commercial air-entraining agent.